Biomimetic Optical Nanostructures: Broadband antireflective coatings for high‐end optical elements. Issue 1 (2nd January 2020) - Weishaupt, Klaus; Diao, Zhaolu; Brunner, Robert; Spatz, Joachim
Abstract: Optical nanostructures have evolved successfully in nature over millions of years. For example, such nanostructures are found on the compound eyes of night active insects. These "moth‐eye" structures offer extraordinary anti‐reflective (AR) properties and therefore allow the insects to hide from their predators. This concept has been transferred to technical applications and enables artificial AR characteristics on high‐end optical elements with performance advantages not possible with classical layer‐based AR coatings. An appropriate manufacturing technology combines self‐organization of nano‐particles with a reactive ion‐etching process.